PENGKAYAAN VITAMIN E PADA PAKAN KOMERSIAL UNTUK PENINGKATAN KEMATANGAN GONAD IKAN NILA - Andriani, Rovina; Abdullah, Nursanti; Muchdar, Fatma; Marus, Ikbal (Journal of Fish Nutrition, 2023)
Tilapia (Oreochomis niloticus) is one of Indonesia's freshwater fish which has economic value. One way to obtain optimal fish hatchery results is by improving reproductive performance, which can be increased by improving the nutritional quality of the parent feed. The nutritional elements that must be present in the main fish feed include vitamin E and fatty acids. Vitamin E has a very important and decisive role in fish reproduction, because Vitamin E functions as an antioxidant which can prevent the oxidation of unsaturated fatty acids in cells and as an antioxidant. Fatty acids present in the cell membrane can accelerate the embryogenesis process to run normally and reproduction results can be increased. Ovagrow is high-quality Vitamin E which is useful for maintaining the egg and sperm maturation process in the parent fish. Ovagrow is also useful for multiplying and improving the quality of eggs and sperm in brood fish. The purpose of this study was to determine the effect of giving different doses of ovagrow to accelerate gonadal maturation of tilapia and to determine the effect of adding ovagrow to gonadal maturity and egg fecundity in tilapia broodstock. The research method used a completely randomized design (CRD) which consisted of 4 treatments with 3 repetitions each. Treatment A ovagrow dose 0.3 gr/1 kg feed, Treatment B ovagrow dose 0.5 gr/1 kg feed, Treatment C ovagrow dose 0.7 gr/1 kg feed and Treatment D ovagrow dose (control) 1 gr/1 kg of feed. The results showed that the TKG of tilapia with the highest percentage was in treatment A and the best fecundity of tilapia was in treatments A and D with a total average value of 541.26. Based on the results of the research conducted, it can be concluded that administration of ovagrow at different doses did not have a significant effect on the gonad maturity level of tilapia broodstock and the average fecundity of tilapia (Oreochoromis niloticus).